Study of therapies for paresthesia in the head and neck region: literature review - Dória, Rafaela Marliano; Dutra, Camila Rodrigues; Queiroz, Guilherme Ribeiro de; Pereira, Cláudio Maranhão (JRG Journal of Academic Studies, 2023)
Paresthesia is an alteration in sensitivity that can be caused after minor oral surgery, trauma, infections, lack of surgical planning, etc. This alteration interferes with the quality of life of patients, as it hinders feeding, phonation and even self-esteem. Paresthesia may be temporary and resolve spontaneously within 6 months or be persistent. In cases where it does not disappear spontaneously, it needs to be treated. Treatment can be done with: medications, physiotherapy, laser therapy, acupuncture and even microneurosurgery. The present work is a literature review that aims to address how the treatment of patients with paresthesia should proceed after minor oral surgery, in order to minimize symptoms and help for a faster and less painful recovery. 25 articles were selected between 2007 and 2023 in the following databases: Google Scholar, PubMed and Scielo. There are several ways to treat paresthesia, each author recommends a type of treatment that was addressed in this literature review. The approach that the dental surgeon will follow depends on each clinical case, but it is always up to the health professional to avoid the appearance of this clinical picture.